Конструкции ветроэнергетических установок при решении проблем промышленной энергетики - Шевченко, Валентина Владимировна; Баженов, А. С.; Лавриненко, Т. А. (Харківський університет Повітряних Сил ім. Івана Кожедуба, 2008)
На основании анализа существующих конструктивных решений и характеристик ветрогенераторов, ветроэнергетических установок в целом рассмотрены вопросы выбора вида генератора, конструкции механической части ветряной установки. Рассмотрены особенности управления, работы, недостатки и преимущества различных генераторов, ветротурбин различных конструкций. Сделан вывод о том, на что целесообразно ориентироваться для Украины в интервале рассматриваемых мощностей и с экономической, и с технической точки зрения.

On the basis of analysis of existent structural decisions and descriptions of wind-generator, wind-energetic plant the questions of choice of type of generator, constructions of mechanical part of the, wind setting, are considered on the whole. Management features, works, failings and advantages of different generators, are considered, wind turbine of different constructions. A conclusion is done about on what it is expedient to be oriented for Ukraine in the interval of the examined powers both from the economic and from technical point of view.
Constructions of power winding plants at the decision of problems of industrial energy
Keywords: типы генераторов; ветрогенераторы; ветроэнергетические установки; ветротурбины; types of generators; wind-generator; wind-energetic plant; wind turbine